O estilo interativo das profissionais do sexo de belo horizonte: um estudo sobre estratégias linguísticas - Gilmar Bueno Santos (2011)
This study aims to reveal the interactive style of the prostitutes that work around the Afonso Pena Avenue, in the south central region of Belo Horizonte. According to the linguistic strategies, we have intended to analyze which aspects contributed for the establishment of negative and positive politeness, and the relation among them in the construction of the social identity of these women. In this work was conducted an ethnographic research, guided by a case study because this method allowed us a detailed investigation about some elements, considering the social context where the prostitutes were situated, giving voice to social actress. The theoretical basis of Goffman (1963, 1967) were used as main reference for the development of data analysis through this work, considering the studies of Brown and Levinson (1987) and Valério (2003) on politeness strategies, and Moita Lopes (2008), Rajagopalan (1998) and Ciampa (1992) in relation to the construction of social identity. Theresults show that the interactive style of these prostitutes was significantly based, on the one hand, adding elements that they consider positive for exercise of prostitution and, on the other, get rid of the stigmas.